The Analysis of Figurative Language in Traitor Song Lyrics - Ida Ayu Putri Gita Ardiantari; Ni Nyoman Sutria Pratiwi (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
The purpose of this research to find out and analyze the types and meaning of figurative language used in Traitor's song lyric. Descriptive qualitative method was used to conduct a clear description of the problem which is identified. The data were taken from Traitor's song lyric by Olivia Rodrigo. The theory proposed by Knickerbocker and Reninger (1963:367) were used to classify the types of figurative language and the theory proposed by Leech (1981) to analyze the meaning of figurative language. The result of this research showed there are four types of figurative language used in Traitor's song lyric, there are simile, personification, hyperbole, and paradox. The researcher found simile are 1 data, personification is 1 data, metaphor is 1 data, and paradox is 1 data.